Comparative study of rice morphological and physiological characteristics of rice grown under organic and inorganic farming - Safrudin, Amad; Dewi, Ratna; Dulbari, Dulbari (Universitas Padjadjaran, 2024)
Organic farming practices have shown a potential to improve rice yields, aside from the popular conventional ones. This study aimed to comparatively analyze the morpho-physiological characteristics of rice plants grown under organic and inorganic farming. This research was conducted at the Polinela Organic Farm experimental station (5°21'10